2018
DOI: 10.1029/2018tc005152
|View full text |Cite
|
Sign up to set email alerts
|

Palinspastic Reconstruction Versus Cross‐Section Balancing: How Complete Is the Central Taurides Fold‐Thrust Belt (Turkey)?

Abstract: In many fold‐thrust belts, cross section–derived shortening estimates are significantly lower than predicted based on plate convergence. This has led to controversial hypotheses that shortening may be largely underestimated due to wholesale underthrusting (convergence without shortening) below far‐traveled continent or ocean‐derived nappes. The Late Cretaceous‐Eocene Taurides fold‐thrust belt (southern Turkey) may contain a highly incomplete shortening record of convergence likely caused by wholesale underthru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…The Maastrichtian to Lutetian cherty pelagic limestones (Kuşca Limestone) also occur in a separate tectonic slice of the Yıldızlı Dağ Unit (Özgül, 1997). On the other hand, McPhee et al (2018) called the same rock assemblages the Geyikdağı nappe, which was deformed by a thin-skinned thrust fault imbricate system that affected the uppermost Mesozoic carbonates and by a deeper thrust duplex system that incorporates Ordovician and older basement rocks. During field work in the Geyik Dağı area, we have observed two carbonate successions of different paleoenvironmental settings separated by faults: one of them contains orbitolinid and rudistid bioclastic limestones of Cenomanian age (cf.…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Maastrichtian to Lutetian cherty pelagic limestones (Kuşca Limestone) also occur in a separate tectonic slice of the Yıldızlı Dağ Unit (Özgül, 1997). On the other hand, McPhee et al (2018) called the same rock assemblages the Geyikdağı nappe, which was deformed by a thin-skinned thrust fault imbricate system that affected the uppermost Mesozoic carbonates and by a deeper thrust duplex system that incorporates Ordovician and older basement rocks. During field work in the Geyik Dağı area, we have observed two carbonate successions of different paleoenvironmental settings separated by faults: one of them contains orbitolinid and rudistid bioclastic limestones of Cenomanian age (cf.…”
Section: Geologic Settingmentioning
confidence: 99%
“…The Cretaceous platform carbonates in the Geyik Dağı area represent a part of the so-called L'Axe Calcaire du Taurus (Ricou et al, 1975), Anatolide-Tauride Carbonate Platform (ATCP) (Şengör and Yılmaz, 1981), Taurus Carbonate Platform (Koçyiğit, 1981), Menderes-Taurus Platform (Görür and Tüysüz, 2001), Menderes Carbonate Platform (Vlahović et al, 2005). Most previous works on the Geyik Dağları range aim to explain its complex geological and tectonic evolution (e.g., Özgül, 1976, 1997; McPhee et al, 2018), except for Özer and Kahrıman (2019), in which Cenomanian canaliculate rudists were documented. In the Anamas-Akseki area, which is the continuation of the Geyik Dağları range to 65 km northwest, there are few studies on the detailed biostratigraphy and facies of the Cretaceous platform carbonate sequences (e.g., Martin, 1969; Monod, 1977; Altıner et al, 1999; Solak et al, 2017, 2019; Solak, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Aladağ and Bolkardağı nappes, and overlying Bozkır nappes, were thrust at least 70 km southwestward over the Geyikdağı nappe, as shown by tectonic windows and klippen (McPhee et al, 2018a). McPhee et al (2018aMcPhee et al ( , 2018b observed that the Geyikdağı nappe is internally deformed and interpreted a thin-skinned style of thrusting based on widespread flat-on-flat thrust contacts, tectonic windows and re-entrants, and klippen. This thrusting produced the Derebucak thrust imbricate toward the foreland (west) and a duplex that is enveloped by the Seydişehir anticline toward the hinterland (east) (Fig.…”
Section: Crustal Architecture Of the Central Anatolia Plateaumentioning
confidence: 99%
“…Structural constraints suggest the Beydağları platform was underthrusted below the Geyikdağı nappe by a minimum of a few kilometers in Eocene time (McPhee et al, 2018a). On the other hand, palinspastic restorations that incorporate paleomagnetic constraints suggest up to some tens of kilometers of Eocene underthrusting (McPhee et al, 2018b).…”
Section: Crustal Architecture Of the Central Anatolia Plateaumentioning
confidence: 99%
See 1 more Smart Citation